The phase composition, structure and properties of high-temperature-based powders of the system iron-aluminum obtained by the technology of the reaction-mechanical alloying. Foundry production and metallurgy - F. G. Lovshenko; A. S. Fedosenko (Литьë и металлургия, 2019)
The regularities of the formation of powders based on the Fe-Al system, obtained by the method of mechanical alloying and intended for the deposition of thermal spraying coatings were established. The morphology, structure, phase composition and properties of materials are investigated. After mechanical synthesis, the powders have an average particle size of 30–100 µm, submicrocrystalline structures, and nonequilibrium phase composition. Annealing of powders causes to an increase in the hardness of particles up to 80%, the value of which is largely preserved after prolonged heating to 1170 K, which indicates the presence of heat-resistant materials.